Optimalisasi Pengelolaan Keuangan Koperasi untuk Pemberdayaan Ekonomi Masyarakat Desa di Cibinong Bogor - Rudy Rahwana (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This research was conducted to obtain information related to the ability of cooperative management to be able to optimize the scale of cooperative business, through efficient, productive and rational capital allocation; utilization of business capacity and cooperative capital; cooperation with various parties, both in the form of business, capital and cooperative management in general; and fertilization of own capital, through member savings and the formation of reserve funds. To achieve the above optimization, the stigma of "Cooperative as an association of people not an association of capital" should be removed, which is often considered as one of the factors causing the failure of cooperative financial management. Of course, this is a tough task for cooperative managers in carrying out their cooperative business activities, but with the capacity of the management that continues to be fostered and upgraded in knowledge and abilities, to achieve maximum cooperative goals.